Predictive factors to avoid farming as a livelihood - H. M. Vinaya Kumar; N. B. Chauhan; D. D. Patel; J. B. Patel (Journal of Economic Structures, 2019)
Farming in India is experiencing a structural change leading to a crisis. The growth rate of agricultural output is steadily declining in recent years. The relative contribution of the farming sector to the total GDP has been decreasing over time increasingly. The present study was conducted in Ahmedabad district of Gujarat, India. Total 100 agricultural landholders from 20 villages were selected to identify factors experienced by them for avoiding farming as a livelihood by employing Ex-Post-Facto research design. It is observed that 'r' computed between factors to avoid agriculture as a livelihood and age (0.589), education (0.330), farming experience (0.250), occupation (0.446), livestock possession (0.207), annual income (- 0.236) was found to be significant at 0.01 level of significance. It could be observed from regression analysis that the personal factors had a powerful effect (0.730) on avoiding agriculture as a profession, influencing in a positive direction. Followed by this, economic factor (0.291) and social factor (0.229) also influenced positively and significantly. The information on the personal, social, economic, psychological, market, situational, labor and next-generation factors experienced by agricultural landholders is analyzed to have in-depth knowledge of each factor. The analyzed suggestions will help to make agriculture a profitable enterprise and attract the farmers and youths to continue the farming activities. The solution to the problem is not in a few packages and programs but in drastic changes in the present policies related to agriculture need to be focused. Other sector's growth and development must not be at the cost of agriculture.
Keywords: 330; Agriculture; Crisis; Farmers; Factors; Livelihood; Sustainability